(3eNJUQ TQM eSGFd Mfjf Hf ESMGb aj GdWHs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg caGA MeOg hGdUdGI Ydi eMeO hBdg , bUOfG aj gPG GdcJGH Cf fSJeQ (B((3?(B) (3eGjMJGL Edjg GdeHJOF HcJGH GdeSGFd dMfjf Hf GSMGb s
(3BNQgG (B:s
(3eHJhQ hGdHhd GdCMeQ EPG de jcf TQH TQGH GMeQ agh jOd Ydi cKQI GdOe aj GdHOf , hgh ai GdCeQGV GdMGOI NjQ ef GdCUaQ hjOd gPG GdHhd Ydi Cf GdeQV CSde , hGdMeO ddg QH GdYGdejf s
(3aj YTQI aUhds
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B221 s
Keywords: (3GdWHs